PERAN PENYULUH TERHADAP AKTIVITAS BUDIDAYA DAN PEMASARAN IKAN LELE DUMBO (Clarias gariepinus) PADA POKDAKAN BAYUR SEJAHTERA DI KELURAHAN SEMPAJA UTARA - Wahyu Abdillah; Nurul Ovia Oktawati; Wahyu Fahrizal (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
This study aimed to analyze the role of fishery exension agent on cultivation activity and marketing of catfish (Clarias gariepinus) on POKDAKAN Bayur Sejahtera based on various criteria including the role of the fishery extension agent as a guide, as an organizer and dynamist, as a field technician, and as a facilitator. This study was analyzed using descriptive analysis and a Likert scale. This study used a case study method. The sample of this study was carried out by census method with a total sample of 26 members of the cultivator group at POKDAKAN Bayur Sejahtera. The results of this study indicate that overall fishery extension agents have a high role in the cultivation activities and marketing of catfish (Clarias gariepinus) in POKDAKAN Bayur Sejahtera with an average score of the total indicators of 49.23 or in the high category. Partially, the role of the extension agent as a guide got an average score of 12.73 or had a high role. The role of the extension agent as an organizer and dynamist got an average score of 12.88 or had a high role. The role of the extension agent as a field technician got an average score of 12.46 or had a high role. Meanwhile, the role of the extension agent as a fasilitator got an average score of 11.15 or had a moderate role. Key Words: Role, Fishery Extension Agent, Fishery Cultivation